The Impact of the Common Law Legal System on Legal Development in Indonesia - Apri Aji Setyawan; Zainal Arifin Hoesein (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This article examines the impact of the common law legal system on the development of law in Indonesia, focusing on how elements of the system have influenced national legal practice and theory. This study uses a qualitative approach through document analysis and literature studies related to the history of Indonesian law and legal practice in common law countries. The results of the study indicate that although Indonesia adheres to a civil law legal system, the influence of common law is visible in certain aspects, such as the principle of precedent, legal interpretation, and the application of customary law. In addition, this study also explores how the integration of common law elements can enrich the dynamics of Indonesian law, especially in the context of legal reform and the achievement of substantive justice. With a better understanding of this influence, it is hoped that recommendations can be produced for the development of a legal system that is more responsive and adaptive to the needs of society.